2017
DOI: 10.1002/aoc.3941
|View full text |Cite
|
Sign up to set email alerts
|

Ni@Pd nanoparticles supported on ionic liquid‐functionalized KCC‐1 as robust and recyclable nanocatalysts for cycloaddition of propargylic amines and CO2

Abstract: Novel heterogeneous catalyst systems comprised of a fibrous nanosilica-supported nano-Ni@Pd-based ionic liquid (KCC-1/IL/Ni@Pd) are described for the cyclization of propargylic amines with CO 2 to provide 2-oxazolidinones.KCC-1 with high surface area was functionalized with IL acting as a robust anchor so that the nano-Ni@Pd was well dispersed on the fibres of the KCC-1 microspheres, without aggregation. Because of the amplification effect of IL, high loading capacities of the nanocatalysts were achieved. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 67 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…In 2016, the group of Yuan-Yao reported the rst protocol for metal-catalyzed three-component cycloaddition of epoxides, amines, and CO 2 under solvent-free condition. 50 In this investigation, various rare-Earth-metal complexes stabilized by amine-bridged tri-(phenolato) ligands (42)(43)(44)(45)(46)(47), co-catalysts (e.g., NBu 4 I, NBu 4 Br, NOCt 4 Br, PPNCl), and additives (e.g., DBU, Et 3 N, TMEDA, DABCO) were examined and the combination of 46/NBu 4 Br/DBU as catalytic system at 95 C was found to be optimal for this transformation. The optimized protocol tolerated a variety of terminal epoxides 48 and both electron-rich and electron-poor anilines 49 and provided the expected 5substituted-3-aryl-2-oxazolidines 50 in moderate to excellent yields (Scheme 22).…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…In 2016, the group of Yuan-Yao reported the rst protocol for metal-catalyzed three-component cycloaddition of epoxides, amines, and CO 2 under solvent-free condition. 50 In this investigation, various rare-Earth-metal complexes stabilized by amine-bridged tri-(phenolato) ligands (42)(43)(44)(45)(46)(47), co-catalysts (e.g., NBu 4 I, NBu 4 Br, NOCt 4 Br, PPNCl), and additives (e.g., DBU, Et 3 N, TMEDA, DABCO) were examined and the combination of 46/NBu 4 Br/DBU as catalytic system at 95 C was found to be optimal for this transformation. The optimized protocol tolerated a variety of terminal epoxides 48 and both electron-rich and electron-poor anilines 49 and provided the expected 5substituted-3-aryl-2-oxazolidines 50 in moderate to excellent yields (Scheme 22).…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 96%
“…Shortly aerwards, Sadeghzadeh, Zhiani, and Emrani introduced a novel nanosilica-supported nano-Ni@Pd-based ionic liquid (KCC-1/IL/Ni@Pd) catalyst for xation of CO 2 into N-propargylamines. 42 The prepared metal-organic framework was employed as an efficient catalyst for carboxylative cyclization of substituted N-propargylamines 29 with CO 2 (1 MPa) at room temperature under neat conditions. Various terminal, internal, primary, and secondary N-propargylamines were effectively used to synthesize functionalized 2-oxazolidinones 30 in high to excellent yields (Scheme 15).…”
Section: Carboxylative Cyclization Of Npropargylamines With Comentioning
confidence: 99%
“…36, the scholars reported an approach for the diuoro alkylation of cinnamic acid by harnessing the photo-redox properties of the reductive capability of a Cu(I) catalyst and a Ru(II) complex. In this work, we showed that DFNS core-shell NPs could be efficiently functionalized using the Pt(II) complex, [37][38][39] which is a novel recoverable heterogeneous nanocatalyst for the environmentally friendly, selective and efficient production of cyclic carbonates from olens and CO 2 , as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…10 Transition Fe-group metals such as Fe, Ni, and Co, among distinct non-noble metals, are generally hybridized using noble metals for creating magnetic NPs that can be simply reproduced utilizing an external magnetic area. [11][12][13][14][15][16] However, cost-effective catalysts of noble metal NPs, which possess great catalytic activities, inactive cores, and effective recoverable properties are extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…4H), 7.51-7.46 (m, 2H), 7.43-7.32 (m, 4H) ppm;13 C NMR (CDCl 3 , 400 MHz) d 196.81, 137.59, 132.45, 130.10, 128.27 ppm. IR (KBr) (cm À1 ): 2961, 2923, 2857, 1653, 1585, 1434, 1310, 1273, 1064, 945, 909; HRMS: m/z calculated for C 13 H 10 ONa + [M + Na + ]: 205.0619, found: 205.0628.…”
mentioning
confidence: 99%